Physico-mechanical properties of glass fibre reinforced biophenolic elastomer composite - Zuhaili Zakaria,; Sarani Zakaria,; Rasidi Roslan,; Chia, Chin Hua; Sharifah Nabihah Syed Jaafar,; Umar Adli Amran,; Gan, Sinyee (Penerbit Universiti Kebangsaan Malaysia, 2018)
In this study oil palm empty fruit bunches (EFB) fibres was used to synthesize biophenolic resin (BPR) at a different formaldehyde/liquefied empty fruit bunches (F/LEFB) molar ratio which is 1.0, 1.5 and 2.0. The higher molar ratio of F/LEFB used has resulted in an increased of viscosity and solid content of BPR resin. The first decomposition of BPR resin occured around 86 to 130°C due to the evaporation of low molecular weight substance which were water, free phenol and formaldehyde. Glass fibre reinforced biophenolic composite (BPC) and glass fibre reinforced biophenolic elastomer composite (BPEC) was successfully fabricated using BPR resin. The impact strength and flexural strain of BPEC were higher than that of BPC. The impact strength of BPEC 1.5 was the highest at 47.71 kJm-2. However, the flexural strength of BPEC was lower compared with BPC, which the highest flexural strength was obtained by BPC 1.0 at 65.18 MPa. The cross-sectional image from scanning electron microscope (SEM) of BPEC and BPC confirmed the presence of epoxidized natural rubber (ENR) improved the compatibility between glass fibre and BPR resin.